INFLUENCE OF SEED INJURY TYPES ON THEIR RESPIRATION INTENSITY DURING STORAGE - Новицкая, Наталия; Гриненко, Любовь; Мартынов, Алексей (SWorldJournal, 2022)
In article shown the results of the study of respiration rate whole and damaged soybean seeds, corn and durum wheat. It was found that the undamaged soybean seeds with high oil content breathe harder than starchy cereals. At damaged cereals seeds highest